Monetary policy, inflation expectations and the price puzzle - Efrem Castelnuovo; Paolo Surico (Bank of Finland, 2009)
This paper re-examines the VAR evidence on the price puzzle and proposes a new theoretical interpretation. Using actual data and two identification strategies based on zero restrictions and model-consistent sign restrictions, we find that the positive response of prices to a monetary policy shock is historically limited to the sub-samples that are typically associated with a weak interest rate response to inflation. Using pseudo data generated by a sticky price model of the US economy, we then show that the structural VARs are capable of reproducing the price puzzle only when monetary policy is passive. The omission in the VARs of a variable capturing expected inflation is found to account for the price puzzle observed in simulated and actual data.
URN:NBN:fi:bof-20140807473
Keywords: 330